EFEKTIVITAS PEMBATALAN PERKAWINAN BERDASARKAN UU NO.16 TAHUN 2019 TENTANG PERUBAHAN ATAS UU NO.1 TAHUN 1974 TENTANG PERKAWINAN DAN IMPLIKASINYA TERHADAP HAK-HAK PASANGAN - Drajat, Ulfah Zakiah; Kahma, Hisma; Subair, Laola; Rezky Apriansyah, Moch. (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2025)
Marriage is not merely uniting two human partners, namely a man and a woman, but rather tying a sacred covenant in the name of Allah, that both bride and groom intend to build a household that is peaceful, tranquil, and filled with love and affection. Marriage is considered something sacred because it has spiritual values, so marriage must be carried out with a series of ceremonies that are religious in nature and performed according to the laws of each religion and belief of the parties who carry out the marriage. At some point in family relationships, there will surely be something that doesn't go according to plan. Marriage can break down along the way, and this can be caused by the parties themselves or by other parties or third parties, making marriage annulment an alternative. Marriage annulment is carried out after the marriage has taken place. A marriage can be annulled if the parties do not meet the requirements to carry out the marriage. Thus, marriage prevention is done before the marriage takes place, while marriage annulment can only be done if the marriage has been carried out. Marriages that violate formal and material requirements can be annulled. Therefore, before a marriage takes place, it is necessary to conduct an examination and preliminary research on the marriage guardian and prospective husband and wife, to determine whether the necessary marriage requirements have been met or if there are obstacles hindering the implementation of the marriage. The formulation of the problem in this thesis is how the mechanism of marriage annulment according to Law Number 1 of 1974 concerning Marriage works and what are the legal implications of marriage annulment on the rights of the couples involved.